Literasi Digital Keluarga dan Prestasi Akademik Anak: Peran Mediasi Pengawasan Orang Tua di Candirejo, Gunungkidul - Andin Prameswari; Lukman Hakim (Universitas Muhammadiyah Mataram, 2025)
Abstract: Digital literacy is a critical component in children's education, yet its correlation with academic achievement in rural family settings like Candirejo Village, Gunungkidul, remains underexplored. The mediating role of family education in this relationship is particularly significant. This study investigates the correlation between family digital literacy and children's academic achievement, emphasizing parental supervision as a key mediator in Candirejo. A descriptive qualitative approach grounded in Husserl's phenomenology was employed. In-depth interviews and participatory observations were conducted with seven children (aged 6-12) and their parents (July-August 2024), data were analyzed using thematic analysis. Digital literacy positively correlates with academic achievement when supported by structured family supervision. However, excessive dependence on smartphones without parental guidance reduces learning motivation in four out of seven children. Children under high supervision demonstrated improved independent learning, while unsupervised use led to distractions from games/social media. Parental digital literacy levels directly influenced supervision efficacy. Families actively mediating digital literacy significantly enhance technology's educational benefits. Collaborative digital literacy training for parents/children and tripartite school-family-community strategies are recommended. Future research should expand to broader populations.Abstrak: Literasi digital merupakan komponen krusial dalam pendidikan anak, namun korelasinya dengan prestasi akademik di lingkungan keluarga pedesaan seperti Kalurahan Candirejo, Gunungkidul, masih terbatas. Peran mediasi pendidikan keluarga dalam relasi ini perlu dikaji mendalam. Menyelidiki korelasi literasi digital keluarga dengan prestasi akademik anak, dengan menekankan pengawasan orang tua sebagai mediator kunci di Candirejo. Pendekatan kualitatif deskriptif berbasis fenomenologi Husserl diterapkan. Wawancara mendalam dan observasi partisipatif dilakukan terhadap tujuh anak (usia 6-12 tahun) dan orang tua (Juli-Agustus 2024), data dianalisis secara tematik. Literasi digital berkorelasi positif dengan prestasi akademik ketika didukung pengawasan keluarga terstruktur. Namun, ketergantungan berlebihan pada ponsel pintar tanpa bimbingan orang tua menurunkan motivasi belajar pada empat dari tujuh anak. Anak dengan pengawasan tinggi menunjukkan peningkatan pembelajaran mandiri, sementara penggunaan tanpa pengawasan mengakibatkan distraksi (game/media sosial). Tingkat literasi digital orang tua berpengaruh langsung pada efektivitas pengawasan. Keluarga yang aktif memediasi literasi digital berperan signifikan dalam memaksimalkan manfaat teknologi. Pelatihan literasi digital kolaboratif (orang tua anak) dan strategi tripartit (sekolah-keluarga-masyarakat) direkomendasikan. Penelitian lanjutan perlu memperluas cakupan populasi.